P128 The role of small bowel capsule endoscopy as a diagnostic tool in isolated complex perianal disease. (30th January 2023) - Avni Biron, I; Ollech, J E; Toth, E; Nemet, A; Wurm Johansson, G; Schweinstein, H; Kopylov, U; Margalit Yehuda, R; Dotan, I; Yanai, H
Abstract: Background: Isolated complicated perianal disease (cPD) might be the sole representation of Crohn's disease (CD). We aimed to evaluate the impact of small bowel capsule endoscopy (SBCE) as a diagnostic tool for CD in this population. Methods: A multicenter, retrospective cohort study from three tertiary centers. Patients with cPD who had a negative workup for CD (Ileocolonoscopy and cross-sectional imaging) and underwent evaluation with SBCE were included. Demographics, biomarkers, and the Lewis inflammatory score (LS) were recorded and analyzed. A LS≥135 was considered a positive SBCE. Results: Ninety-one patients were included: 65 males (71.4%), mean age 40 (14) years, median duration of cPD 25.13 months (12.53-66.1). SBCE was positive in 24 patients (26.37%). Median LS was 675 (222-1518). Fecal calprotectin (FC) positively correlated with LS (r=0.81; p<0.0001): patients with a positive vs. negative SBCE had a significantly higher mean FC level (255 [389] vs 97[180], p=0.02), Figure 1. Correspondingly, a FC level ≥ 300 mg/kg had a specificity of 90% for a positive SBCE, while a cutoff of FC level <100 mg/kg or <50 mg/kg had a sensitivity of only 40% or 50% to rule out small bowel CD, respectively. Conclusion: SBCE was positive in over a quarter of patients with cPD and a negative workup for CD. FC levels correlated with the degree of inflammation defined by the LS. However, the sensitivity of low FC to rule out CD was low. These results suggest that SBCE is an essential diagnostic tool for patients with cPD even after negative workup.